IOM Recognized as Main Data Provider in IASC’s Management Response to Independent Review of Humanitarian Response to Internal Displacement - IOM (International Organization for Migration, 2024)
The International Organization for Migration (IOM) welcomes the recognition of its Displacement Tracking Matrix (DTM) as a lead provider of country-level data on internal displacement in the Inter-Agency Standing Committee (IASC) Management Response to the Independent Review of the Humanitarian Response to Internal Displacement